Molecular identification of some Bursaphelenchus populations with the aid of PCR-RFLP of rDNA - JIANG Li-qin; LIANG Ding-dong; ZHENG Jing-wu; GU Jiang-feng; YANG Lan-ying (浙江大学学报. 农业与生命科学版)
Six populations of genus Bursaphelenchus isolated from pine wood produced in China, Japan and Korea were identified with the aid of PCR-RFLP of rDNA. It was bound that one of the populations, which had its origin in the forests of Zhenhai, Zhejiang Province, China, and the other, which was derived from imported coniferous wood packages produced in Japan were both identified as B. xylophilus. The other four populations, including populations from Fuyang of the Zhejiang Province, Korea, Hongkong and Japan, were identified as B. mucronatus. All the four restriction enzymes, namely Hinf Ⅰ, Hae Ⅲ, Msp Ⅰ, and Cfo Ⅰ, with their special sites of cutting could be used to differentiate the two morphologically very similar species.